Effect of a cement-lignin agent on the shear behavior of Shanghai dredged marine soils. Issue 1 (2nd January 2017) - Liu, Wenbai; Chen, Qingsheng; Chiaro, Gabriele; Jiang, Hongming
ABSTRACT: With the rapid urbanization in Shanghai, China, suitable fill materials have been reported to be in great shortage in recent years. A prospective solution to these issues is to convert the huge amount of existing dredged marine soils to construction materials via solidification. However, there have been no studies on the shear behavior of solidified dredged materials from Shanghai region so far, while it has been reported by various researchers that the available data obtained from certain types of clay cannot be confidently and readily applied to other types of soils. To address this challenging issue, in this article, samples of Shanghai marine dredged soils were retrieved from the world's largest reclamation project in Shanghai Lin-gang New City. A series of laboratory tests have been conducted to investigate the shear behavior of Shanghai dredged marine soils solidified using a new composite curing agent made of cement and lignin. The test results and the effect of this cement–lignin agent on the shear behavior of Shanghai marine soils, including the stress–strain behavior, shear strength properties, and failure characteristics are presented and discussed, which can provide valuable reference for the use of dredged soils as construction materials in the Shanghai region.